Design of switchable dual-band bandpass filter for wireless communication - Yully Erwanti Maskurin (2018)
Due to the progression growth of multiservice wireless communication systems in a single device, multiband bandpass filter has attract a great attention to the end user. Therefore, multiband bandpass filter is a crucial component in the multiband transceivers systems which can support multiple services in one device. Multiband bandpass filter with wideband passband has been drawing a lot of interests of researcher to carry out innovative synthesis and techniques designing the multi-band bandpass filters with less complexity, minimal cost and high performance. Therefore, this thesis presents new technique in designing the switchable dual-band bandpass filter at 2.4 GHz and 3.5 GHz for WLAN and WiMAX applications. Firstly, the wideband bandpass filter was designed centred at frequency of 3 GHz. This filter was constructed by employing the topology of stepped impedance resonator (SIR). This method offer various benefits for instance minimizing the number of elements and transmission zeroes are achieved. As a way to eliminate the interference from existing system that operates in the frequency band, a defected microstrip structure (DMS) was applied and implemented to produce a wide notch band. As the DMS was integrated to the bandpass filter, the dual passband was produced centred at 2.55 GHz and 3.48 GHz with 3 dB bandwidth of 19.6 % and 18.7 %, respectively. In order to generate the switchable characteristic, the PIN diode was introduced at the dual-band bandpass filter. It exhibits that the measured results for switchable attributes when the diode is at OFF state, the wide passband is produced with the fractional bandwidth of 62.1 % centred at 2.9 GHz. Meanwhile, for the diode in ON state, the dual-passband has produced which centred at 2.5 GHz and 3.45 GHz. The first passband possess the fractional bandwidth of 24 % while the second passband is 20.3 %.This structure is very useful for wireless communication systems and applications as it can be easily integrated with other planar devices. Advanced Design System (ADS) software was used to simulate the design from circuit element to physical momentum realization. The experimental results showed good agreement with the simulated results. The benefits of the integrated band-pass filter and defected structure are the reduction of the overall size and ease to fabricate.